HYPERDIAGNOSIS OF TUBERCULOSIS IN PATIENTS WITH LUNG MALIGNANCIES - Zh. A. Laushkina; P. N. Filimonov (Туберкулез и болезни лёгких)
The paper shows problems in the differential diagnosis of malignancies of the lung and pleura in 55 patients. It characterizes the duration of a diagnostic period in patients with lung cancer identified at all diagnostic stages in tuberculosis hospitals. The clinical manifestations of lung malignancies are shown. The predictors of delay in the verification of diagnosis are found.